1985
DOI: 10.1152/ajpheart.1985.248.1.h33
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic modulation of acetylcholine release from cardiac parasympathetic neurons

Abstract: Acetylcholine can be released from parasympathetic nerve endings in rat atria by 57 mM K+ depolarization or by electrical field stimulation. We have studied the presynaptic modulation of [3H]acetylcholine release from superfused rat atria prelabeled with [3H]choline. Exogenous acetylcholine and the specific muscarinic agonist oxotremorine inhibit the stimulation-induced overflow of [3H]acetylcholine into the superfusion medium. The half-maximal inhibitory concentration (IC50) of oxotremorine is 0.3 microM. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 0 publications
4
36
0
Order By: Relevance
“…Such receptors have previously been described in the cardiac nerves in the rat (Wetzel & Brown, 1985) and in the guinea-pig (Jeck et al, 1988). Blockade of these receptors by gallamine would increase transmitter output from the vagus nerves and increase the concentration of antagonist required to inhibit vagallyinduced bradycardia.…”
Section: Discussionmentioning
confidence: 86%
“…Such receptors have previously been described in the cardiac nerves in the rat (Wetzel & Brown, 1985) and in the guinea-pig (Jeck et al, 1988). Blockade of these receptors by gallamine would increase transmitter output from the vagus nerves and increase the concentration of antagonist required to inhibit vagallyinduced bradycardia.…”
Section: Discussionmentioning
confidence: 86%
“…This result is in keeping with previous studies which have shown that low-dose atropine amplifies vagal cardiac efferent activity (16, 17). Previous studies have demonstrated that the negative chronotropic action of atropine is mediated by both central (18, 19) and peripheral (20)(21)(22) mechanisms. Vertebral interspace variation in the antimuscarinic action of atropine, the effects of anesthesia, and the doses of atropine used in the studies make it difficult to extrapolate previously obtained results to human studies.…”
Section: Effects Of Low-dose Atropine On Cardiac Vagal Activitymentioning
confidence: 99%
“…In these tissues, the receptors are located in the ganglia (Suzuki & Volle, 1979;Gallagher et al, 1982;Morita et al, 1982;Ashe & Yarosh, 1984) and on the postganglionic final nerve terminals (Loffelholz & Muscholl, 1970;Kilbinger & Wagner, 1979;Fox et al, 1985;Wetzel & Brown, 'Author for correspondence. 1985).…”
Section: Introductionmentioning
confidence: 99%